(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2020)
Genetically modified organisms are one of the most innovative products in the food sector and, also, one of the most controversial scientific “phenomena”. They have important potential for development and sustainability, but they also involve risks related to the necessary safety standards, the maintenance of certain quality levels of the product and the consumer protection. The essay aims to analyse the regulations on GMO, at national and European level, trying to clarify and understand the current opportunities and problems that actually exist today with regard to the category of genetically modified organisms (including the the most recent gene editing techniques).